It Is Feasible to Produce Olive Oil in Temperate Humid Climate Regions - Conde-Innamorato, Paula; Arias-Sibillotte, Mercedes; Villamil, Juan José; Bruzzone, Juliana; Bernaschina, Yesica; Ferrari, Virginia; Zoppolo, Roberto; Villamil, José; Leoni, Carolina (Frontiers in Plant Science, 2019)
Worldwide olive industry has expanded into new climatic regions outside the Mediterranean basin due to an increase in extra virgin olive oil demand posing new challenges. This is the case of Uruguay, South America, where the olive crop area reached 10,000 hectares in the last 15 years and is intended to the production of EVOO. Uruguay has a temperate humid climate with mean precipitations above 1,100 mm per year but unequally distributed, mild winters, and warm summers, with mean annual temperatures of 17.7°C. Different agroecological conditions require local knowledge to achieve good productivity whereby the objective of this work was to show the feasibility and potential of olive oil production under our climatic conditions. For this the agronomic performance of Arbequina, Barnea, Frantoio, Leccino, Manzanilla de Sevilla, and Picual cultivars was evaluated along 10 years of full production. Phenology behavior, vegetative growth rate, productive efficiency, alternate bearing, and oil yield were determined. Sprouting and flowering processes occur in a wide window within the annual cycle between the months of August to November with great interannual variation. More than 8 t/ha fruit yield and 40% oil yields in dry weight basis were obtained in promising cultivars. However, alternate bearing arose as the main production limiting factor, with ABI values greater than 0.60 for most cultivars. We conclude that olive oil production in humid climate regions is feasible and the most promising cultivars based on productive efficiency are Arbequina and Picual.